2018
DOI: 10.1016/j.colsurfb.2018.02.048
|View full text |Cite
|
Sign up to set email alerts
|

pH driven precipitation of quisinostat onto PLA-PEG nanoparticles enables treatment of intracranial glioblastoma

Abstract: Histone deacetylases (HDACs) are known to be key enzymes in cancer development and progression through their modulation of chromatin structure and the expression and post-translational modification of numerous proteins. Aggressive dedifferentiated tumors, like glioblastoma, frequently overexpress HDACs, while HDAC inhibition can lead to cell cycle arrest, promote cellular differentiation and induce apoptosis. Although multiple HDAC inhibitors, such as quisinostat, are of interest in oncology due to their poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 51 publications
1
31
0
Order By: Relevance
“…molecules within nanoparticles can increase delivery, reduce toxicities, and enhance CNS activity, even when nanoparticles have not been designed for specific passage across the bloodbrain barrier (Cook et al, 2015;Householder et al, 2015Householder et al, , 2018. Importantly, our prior studies demonstrated neuroprotective effects of adapalene in primary spinal motor neuron cultures (Kolarcik and Bowser, 2012) and we hypothesized a nanoparticle formulation would also have low to no toxicity in vivo.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…molecules within nanoparticles can increase delivery, reduce toxicities, and enhance CNS activity, even when nanoparticles have not been designed for specific passage across the bloodbrain barrier (Cook et al, 2015;Householder et al, 2015Householder et al, , 2018. Importantly, our prior studies demonstrated neuroprotective effects of adapalene in primary spinal motor neuron cultures (Kolarcik and Bowser, 2012) and we hypothesized a nanoparticle formulation would also have low to no toxicity in vivo.…”
Section: Discussionmentioning
confidence: 93%
“…Our lab previously demonstrated that delivery of drugs from polymeric nanoparticles can improve the efficacy of therapeutic candidates while reducing toxicity for the treatment of intracranial tumors via enhancements in bioavailability (Zhou et al, 2013;Cook et al, 2015;Householder et al, 2015Householder et al, , 2018. We have previously studied the fate of intravenously administered nanoparticles and encapsulated payloads in the central nervous system, demonstrating that delivery of hydrophobic payloads to the brain and spinal cord can be achieved even if the nanoparticles have not been designed for BBB passage (Cook et al, 2015;Medina et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13] We and others have developed nanoparticle encapsulation strategies to improve drug tolerability, pharmacokinetics, and site-specific delivery of HDAC inhibitors. [14][15][16][17] However, each of these reports has developed approaches for encapsulation of individual HDAC inhibitors, requiring development of unique loading strategies for individual drugs. These intensive efforts have thus far yielded only modest loading.…”
Section: Introductionmentioning
confidence: 99%
“…Although these quisinostat loaded PLA-PEG nanoparticles were highly loaded and useful for treating intracranial glioblastoma by intravenous injection, in vitro studies demonstrated that drug was released rapidly once nanoparticles were exposed to an aqueous environment. 14 Presumably this rapid release occurred because quisinostat was only associated with the surface of the nanoparticle, instead of being embedded within a particle core.…”
Section: Introductionmentioning
confidence: 99%
“…In the past few decades, biomedical research has focused more and more on DDS research. 26 A variety of nanocarriers have been widely developed and used, for example, poly(d, l-lactide)-b-methoxy poly(ethylene glycol) (PLA-PEG) 27 and layer-by-layer microcarriers, 28 which loads the chemicals or protein drugs with the same chemical property (oppositely charged bio-polyelectrolytes). However, carriers capable of carrying two different chemical properties at the same time are rare.…”
Section: Introductionmentioning
confidence: 99%